Highly Efficient and Water‐Insensitive Self‐Healing Elastomer for Wet and Underwater Electronics. (6th April 2020) - Khatib, Muhammad; Zohar, Orr; Saliba, Walaa; Srebnik, Simcha; Haick, Hossam
Abstract: Integrating self‐healing capabilities into soft electronic devices increases their durability and long‐term reliability. Although some advances have been made, the use of self‐healing electronics in wet and/or (under)water environments has proven to be quite challenging, and has not yet been fully realized. Herein, a new highly water insensitive self‐healing elastomer with high stretchability and mechanical strength that can reach 1100% and ≈6.5 MPa, respectively, is reported. The elastomer exhibits a high (>80%) self‐healing efficiency (after ≈ 24 h) in high humidity and/or different (under)water conditions without the assistance of an external physical and/or chemical triggers. Soft electronic devices made from this elastomer are shown to be highly robust and able to recover their electrical properties after damages in both ambient and aqueous conditions. Moreover, once operated in extreme wet or underwater conditions (e.g., salty sea water), the self‐healing capability leads to the elimination of significant electrical leakage that would be caused by structural damages. This highly efficient self‐healing elastomer can help extend the use of soft electronics outside of the laboratory and allow a wide variety of wet and submarine applications. Abstract : Smart polymer design can be used to combine both a highly flexible and hydrophobic domain with a hard and dynamic one. This results in a highly water‐insensitive and self‐healing elastomer that can be used for soft electronic applications that work in both ambient and aqueous conditions and show great self‐healing capabilities in terms of electrical and mechanical properties.